Optimalisasi Media Game Digital dalam Game Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis pada Pelajaran IPA - Fitanti, Sinta Yuni; Prahani, Binar Kurnia; Suryanti, Suryanti; Saphira, Hanandita Veda (Universitas Negeri Surabaya, 2025)
Objective: This study has the objective to analyze the implementation of a game-based learning model in improving the critical thinking skills of elementary school students in learning science material on energy sources, focusing on the implementation of learning, the effectiveness of improving critical thinking skills, and student responses. Method: The research method used is quantitative with an experimental design of control group pretest posttest design involving 90 fourth grade students who are divided into three groups: experiment 1 using the digital game